1983
DOI: 10.1146/annurev.nu.03.070183.001313
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine

Abstract: Carnitine has a critical role in energy metabolism. Many of the functions of carnitine are not clearly elucidated and many of the regulatory mechanisms governing carnitine metabolism are ill-defined. Carnitine deficiency can be life threatening but may be resolved with carnitine supplementation. Various groups of individuals in addition to those with the classical carnitine deficiency syndrome may require exogenous carnitine. Carnitine nutriture can no longer be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
5

Year Published

1985
1985
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(97 citation statements)
references
References 0 publications
0
92
0
5
Order By: Relevance
“…The patient, weighing 73 kg, selected a palatable diet, normal for him, and adhered to the same menu for 7 d. The diet was free of meat and, therefore, essentially devoid of creatine and creatinine and very low in N-methylhistidines (37) and carnitine (38). It contained 3,014 calories, 87.7 g of protein, 11.2 mmol methionine, 9.3 mg-atom cystine sulfur, and 3.6 mmol choline.…”
Section: Resultsmentioning
confidence: 99%
“…The patient, weighing 73 kg, selected a palatable diet, normal for him, and adhered to the same menu for 7 d. The diet was free of meat and, therefore, essentially devoid of creatine and creatinine and very low in N-methylhistidines (37) and carnitine (38). It contained 3,014 calories, 87.7 g of protein, 11.2 mmol methionine, 9.3 mg-atom cystine sulfur, and 3.6 mmol choline.…”
Section: Resultsmentioning
confidence: 99%
“…For example, carnitine is the requisite carrier for the transport of long-chain fatty acids across the inner mitochondrial membrane into the mitochondrial matrix [7]. In muscle, carnitine concentration decreases with advancing age [8][9][10].…”
mentioning
confidence: 99%
“…Hoffman et al (1993) reported no improvement in energy utilisation in neonatal and young pigs fed L-carnitine. However, previous studies (Broquist, 1982;Borum, 1983;Bremer, 1983;Rebouche and Paulson, 1986), showed that added L-carnitine improved fat utilisation, especially fatty acids in (3-oxidation in mammals. Also Cho et al (1999a) reported that L-carnitine improved the crude fat and gross energy digestibility in starter piglets.…”
Section: Nutrien T Digeslibuitymentioning
confidence: 94%